Configuration and Motion Modeling of a New Parallel Machine Tool Based on 3-RRRS Mechanism - Chunmei Pan; Ruolan Wang; Liwei Li; Liangwen Wang; Yalei Shi; Shizhao Zhang (Jixie chuandong)
A novel parallel machine tool configuration is presented based on 3-RRRS mechanism. RRRS refers to kinematic pairs of a branched chain consisting of three R-pairs and an S-pair. The 3-RRRS mechanism connects a moving platform between top and bottom platforms，by which the six-dimensional motion of the moving platform relative to the bottom platform can be achieved. A power head installed on the moving platform completes the machining operation of the machine tool. Each R-pair in RRRS motion branch chain is equipped with a drive power where each motion consists of 3 drive pairs. The whole motion branch chain system has 9 driver variables and possesses sub-driver features，which make the parallel machine tool have a larger workspace and better motion and dynamic characteristics. Firstly，the modular structure of the novel machine tool is introduced. Secondly，the modeling analysis of the machine tool based on 3-RRRS mechanism is carried out and the motion and control models of each mechanism variables are given in machine tool operation. Finally，the calculation example is given and the result is verified by using a motion simulation. The related works provide a theoretical basis for the practical use of subsequent equipment.